Analysis of the Impact of Green Policy and Environmentally Friendly Supply Chain Management on Competitive Advantage through Green Technology Adaptation as an Intervening Variable in Manufacturing Companies in North Sumatra - Hastuti Handayani Harahap; Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the impact of green policies and environmentally friendly supply chain management on the competitive advantage of manufacturing companies in North Sumatra through the adaptation of green technology as an intervening variable. The method used in this study is quantitative with the Structural Equation Modeling (SEM) approach using Smart PLS software. The data used in this study were obtained through a survey involving manufacturing companies in North Sumatra. The results of the study indicate that green policies and environmentally friendly supply chains have a significant effect on the adaptation of green technology, which in turn has a positive impact on the company's competitive advantage. This study also found that the adaptation of green technology acts as a mediator that strengthens the relationship between green policies, environmentally friendly supply chains, and competitive advantage. These findings indicate that manufacturing companies that implement green policies and manage their supply chains with an environmentally friendly approach can strengthen their competitive position through more efficient and environmentally friendly technological innovations. The implication of this study is the importance of green policies that support the adoption of green technology and environmentally friendly supply chain management in increasing the company's competitiveness in an increasingly competitive market.